2009
DOI: 10.1242/jeb.024950
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements of laterally eyed birds are not independent

Abstract: SUMMARYMost birds have laterally placed eyes with two largely separated visual fields. According to studies in pigeons laterally eyed birds move their eyes independently in most situations, eye coordination just occurred during converging saccades towards frontal stimuli. Here we demonstrate for the first time that laterally eyed zebra finches show coordinated eye movements, regarding direction and amplitude. Spontaneous and visually elicited movements of the two eyes were recorded simultaneously, using a newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Similar weakly yoked saccades have also been found in phylogenetically distant species within Accipitriformes and Caprimulgiformes (Wallman and Pettigrew, 1985). However, the weakly yoked saccades are different from the conjugate or strongly yoked saccades present in other Passeriformes, like the zebra finch (Voss and Bischof, 2009). Functionally speaking, weakly yoked saccades could actually be deemed similar to independent saccades.…”
Section: −1supporting
confidence: 59%
See 4 more Smart Citations
“…Similar weakly yoked saccades have also been found in phylogenetically distant species within Accipitriformes and Caprimulgiformes (Wallman and Pettigrew, 1985). However, the weakly yoked saccades are different from the conjugate or strongly yoked saccades present in other Passeriformes, like the zebra finch (Voss and Bischof, 2009). Functionally speaking, weakly yoked saccades could actually be deemed similar to independent saccades.…”
Section: −1supporting
confidence: 59%
“…A horizontal eye movement axis, which has previously been found in chickens (Schwarz et al, 2013) and zebra finches (Voss and Bischof, 2009), would allow birds to keep their centers of acute vision along the prominent horizon. However, contrary to our expectations, we found that European starlings primarily move their eyes along a tilted axis (13.46 deg) (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations